REFLECTIONS FROM THE PERSON OF THE EDUCATOR: PHYSICAL EDUCATION AND WEIGHTINGS FROM A PROCESS OF CHANGE CONFERENCE OF EDUCATIONAL WORK (Fiep Bulletin - online, 2012)
This research is part of the school context in which the teacher is the guy who fits with the practice teacher permeated by personal beliefs and the relationships you have with the other actors school, both for the convictions of the area in which it operates or the human relations with which it engages. The main objective is to observe focuses specifically in the area of Physical Education, whose recent history has given her new perspectives of teaching, how the teacher handles situations that lead to change both his speech and his practice. For both the theoretical discussions are based on reflections on the speeches of two teachers of Physical Education, basic education, followed for 6 months. This analysis is based on different theoretical, where the discussion goes back to teaching practice that is permeated by different aspects directly linked to these establish the relationship with his acting, 'watching and reflecting, "and pointing to a consistent and relevant teaching. The results show that the different profiles of the teachers directly affect involvement with issues ranging from organization of classes, the choice of the themes proposed in the area to be long-term planning of the course, until the relationship with the student, that which has had been established. These emerging signs of change in methodology of teaching offered to students as well as commitment, security or insecurity of the group of subjects who engage in this reflection process. Thus it is perceived to be a time devoted to reflection on your area of teaching, the teacher provides a more secure and motivating to their area of expertise.
Keywords: Physical Education Teachers Performances; Reflective Practice